The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/0100-29452019092
|View full text |Cite
|
Sign up to set email alerts
|

Quality of ‘Tainung 1’ papaya produced by partial root zone drying

Abstract: Resumo A significant portion of papaya production in the state of Minas Gerais originates from irrigated crops, and irrigation management using the partial root zone drying technique (PRD) is a fundamental alternative to reduce water waste. This study aimed to evaluate the quality of ‘Tainung 1’ papaya produced under PRD in semi-arid conditions of northern state of Minas Gerais. PRD treatments were composed of reduction of the calculated irrigation water (CIW) by 50%, applied on one side of the irrigation lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Although several studies have been conducted on the PRD technique, there are still knowledge gaps for different types of soil, climate and crops, to determine the feasibility of the PRD technique to farmers 17 , 18 , especially for some fruit trees, such as papaya 10 , 13 , 19 . Few studies have considered PRD techniques in papaya plants under controlled conditions (i.e., under greenhouse condition 9 , 10 ), while PRD studies under papaya field conditions have just recently started 10 , 13 , 19 , 20 . This study reported that the PRD technique using irrigated side alternation frequency each 7–14 days with a 35% reduction in the irrigation depth could be a feasible technique to increase water use efficiency under semi-arid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have been conducted on the PRD technique, there are still knowledge gaps for different types of soil, climate and crops, to determine the feasibility of the PRD technique to farmers 17 , 18 , especially for some fruit trees, such as papaya 10 , 13 , 19 . Few studies have considered PRD techniques in papaya plants under controlled conditions (i.e., under greenhouse condition 9 , 10 ), while PRD studies under papaya field conditions have just recently started 10 , 13 , 19 , 20 . This study reported that the PRD technique using irrigated side alternation frequency each 7–14 days with a 35% reduction in the irrigation depth could be a feasible technique to increase water use efficiency under semi-arid conditions.…”
Section: Introductionmentioning
confidence: 99%